2021
DOI: 10.1038/s41598-021-97988-9
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a novel injectable hydrogel for protecting artificial gastrointestinal ulcers after endoscopic resection: an animal pilot study

Abstract: Recently, covering materials for protecting post-endoscopic ulcers are being developed using hydrogels. Existing hydrogels are not ideal coating materials because it is difficult to control their physical properties. Therefore, we conducted an animal pilot study to investigate the protective effect of a novel ulcer coating material, whose physical properties can be easily controlled and designed. We applied the novel injectable hydrogel to artificial ulcers induced on the gastric mucosa of rats. Rats were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Several studies showed the hemostatic utility of SAPs following endoscopic mucosal resection or ESD for diverse gastrointestinal lesions ( Yoshida et al, 2014 ; Pioche et al, 2016 ; Subramaniam et al, 2019 ). Hydrogels are also being developed and show promising results ( Miura et al, 2021 ). In addition to having a hemostatic function, SAPs were reported to facilitate ulcer healing within the first week and increase the scarring rate at 4 and 8 weeks after ESD ( Uraoka et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the hemostatic utility of SAPs following endoscopic mucosal resection or ESD for diverse gastrointestinal lesions ( Yoshida et al, 2014 ; Pioche et al, 2016 ; Subramaniam et al, 2019 ). Hydrogels are also being developed and show promising results ( Miura et al, 2021 ). In addition to having a hemostatic function, SAPs were reported to facilitate ulcer healing within the first week and increase the scarring rate at 4 and 8 weeks after ESD ( Uraoka et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…PEG-based hydrogels containing crosslinked symmetrical tetra-arm macromonomers, of the same size, form homogenous structures with substantial mechanical strength comparable to natural cartilage [ 35 ]. Therefore, many studies report the use of multi-arm PEG as the base material due to its biocompatibility, ease of manufacturing, and high mechanical strength ( Figure 3 A) [ 27 , 36 , 37 , 38 , 39 ]. For example, a tetra-arm PEG-amine (NH 2 ) gels with a NHS functionalized PEG (NHS-PEG-NHS) in 100 s [ 27 ]; a tetra-arm PEG with end-capped thiols (SH) gels with a tetra-arm PEG-maleimide through a thiol-ene reaction in 4 min [ 36 ]; a tetra-arm PEG-NH 2 and a tetra-arm PEG-aldehyde (CHO) gel through Schiff base reactions in 25 s [ 37 ].…”
Section: Acute Gi Bleedingmentioning
confidence: 99%
“…Therefore, many studies report the use of multi-arm PEG as the base material due to its biocompatibility, ease of manufacturing, and high mechanical strength ( Figure 3 A) [ 27 , 36 , 37 , 38 , 39 ]. For example, a tetra-arm PEG-amine (NH 2 ) gels with a NHS functionalized PEG (NHS-PEG-NHS) in 100 s [ 27 ]; a tetra-arm PEG with end-capped thiols (SH) gels with a tetra-arm PEG-maleimide through a thiol-ene reaction in 4 min [ 36 ]; a tetra-arm PEG-NH 2 and a tetra-arm PEG-aldehyde (CHO) gel through Schiff base reactions in 25 s [ 37 ]. All three hydrogel formulations exhibit high storage moduli of over 5 kPa, good adhesive strengths of around 10 kPa, comparable to commercially available adhesives, and short in situ gelation time within 5 min, enabling rapid hemostasis [ 40 ].…”
Section: Acute Gi Bleedingmentioning
confidence: 99%
“…9,10 The network uniformity is a distinguishable feature of tetra gels from the other network polymers, and the studies based on the uniformity have been made both toward fundamental and application directions. 11–15…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The network uniformity is a distinguishable feature of tetra gels from the other network polymers, and the studies based on the uniformity have been made both toward fundamental and application directions. [11][12][13][14][15] An interesting approach is to utilize tetra gels as reference materials for studying the effects of defects. Sakai et al 16 have conducted such an attempt using tetra gels made of prepolymers with the arm length contrast.…”
Section: Introductionmentioning
confidence: 99%